A vibration powered wireless mote on the Forth Road Bridge. (November 2015) - Jia, Yu; Yan, Jize; Feng, Tao; Du, Sijun; Fidler, Paul; Soga, Kenichi; Middleton, Campbell; Seshia, Ashwin A
Abstract: The conventional resonant-approaches to scavenge kinetic energy are typically confined to narrow and single-band frequencies. The vibration energy harvester device reported here combines both direct resonance and parametric resonance in order to enhance the power responsiveness towards more efficient harnessing of real-world ambient vibration. A packaged electromagnetic harvester designed to operate in both of these resonant regimes was tested in situ on the Forth Road Bridge. In the field-site, the harvester, with an operational volume of ∼126 cm 3, was capable of recovering in excess of 1 mW average raw AC power from the traffic-induced vibrations in the lateral bracing structures underneath the bridge deck. The harvester was integrated off-board with a power conditioning circuit and a wireless mote. Duty- cycled wireless transmissions from the vibration-powered mote was successfully sustained by the recovered ambient energy. This limited duration field test provides the initial validation for realising vibration-powered wireless structural health monitoring systems in real world infrastructure, where the vibration profile is both broadband and intermittent.